Cancer Survivorship in Latin America: Current Status and Opportunities. (2021) - Anampa-Guzmán, Andrea; Acevedo, Francisco; Partridge, Ann H.; Alfano, Catherine M.; Nekhlyudov, Larissa
Abstract : PURPOSE: The number of cancer survivors is increasing globally although the status of cancer survivorship care provision and research in developing countries is limited. This study aimed to review published literature and available guidelines and/or recommendations to inform cancer survivorship care in Latin America. METHODS: Embase, Web of Science, Scopus, PubMed, and SciELO were systematically searched for articles and guidelines and/or recommendations published through December 31, 2020. Our search terms included cancer, survivors, neoplasm, cancer, survivorship, survivor, follow-up studies, and the name of the countries. We categorized the articles by country, year, cancer type(s), language, and domain of cancer survivorship care. We also searched governmental health agencies websites in all Latin American countries. RESULTS: Our literature review found 664 articles for inclusion. The number of publications increased over time. Brazil had most of the survivorship research (n = 483, 72.7%). The most common topics included surveillance and management of psychosocial effects (n = 237, 35.7%) and physical effects (n = 230, 34.6%). Prevention and surveillance for recurrences and health promotion and disease prevention were each addressed by about 10% (n = 71) of the publications. Although close to half of the publications included more than one cancer, 28.9% (n = 192) focused solely on breast cancer. We found no guidelines and/or recommendations explicitly focusing on Latin America in the reviews of the literature or the national governmental institutions' websites. CONCLUSION: We found a growing body of cancer survivorship publications, mainly focusing on psychosocial and physical effects, although no cancer survivorship guidance and/or recommendations focused on Latin America were identified. Expanding research across Latin American countries and covering a broader spectrum of cancer survivorship care is needed. Development of guidelines may further promote provision of quality care for this growing population of cancer survivors.